Qualitative analysis of patient responses to the ABCD FreeStyle Libre audit questionnaire. (17th April 2019) - Overend, Louise; Simpson, Emma; Grimwood, Tom
Abstract: The Abbott FreeStyle Libre flash glucose monitoring system is a novel sensor‐based, factory‐calibrated device that allows individuals with diabetes to monitor their interstitial glucose levels, capture up to 8 hours of interstitial glucose data, and predict future changes in interstitial glucose by scanning a temporary implantable glucose sensor with a reader device or compatible mobile phone. The study aim was to determine whether use of a flash glucose monitoring system had an impact on quality of life and to explore why this was the case. Raw data were collected as part of a brief semi‐structured interview supported by the ABCD FreeStyle Libre Follow‐Up Visit Data Collection form. Data were collected pragmatically at outpatient clinic follow‐up visits, and the first 40 patients to complete six months of continuous use were included in the study. Feedback on use of the device was overwhelmingly (although not unanimously) positive. A number of basic themes were identified independently by the investigators, which were then grouped into four organising themes: Contrast with capillary blood glucose monitoring; Impact on hypoglycaemia experience; Glycaemic control and complications; and Improved wellbeing and quality of life. These themes are analysed and illustrated in the article. Copyright © 2019 John Wiley & Sons.